Implementasi Pembelajaran Matematika Melalui Model Discovery Learning Berbasis Multimedia Ditinjau Dari Kreativitas Matematika Siswa Kelas VIII SMP Negeri 1 Grobogan Tahun Ajaran 2014/2015 - Majidahayu, Ghanies (2015)
The aim of research to analyze: (1) the effect of the use of multimedia-based learning models of Discovery to students' learning achievement, (2) the influence of mathematical creativity toward student learning achievement, (3) the interaction between the mathematical model of learning and creativity on students' math learning achievement. The study population was the entire second semester of eighth grade students of SMP Negeri 1 Grobogan academic year 2014/2015. The research sample that is class VIII.9 as an experimental class that is subject learning model of Discovery Learning multimedia-based and grade VIII.6 as a control class with conventional learning model. Sampling studies using cluster random sampling technique. Data collection methods consisted of achievement tests, questionnaires, observation, and documentation. Data were analyzed using analysis of variance test with two different cell lines, with the prerequisite test analysis Lilliefors method to test for normality and Bartlett's homogeneity test methods. From the results of data analysis with significance level of 5% was obtained results: (1) There are effects of learning with multimedia-based learning models of Discovery with the conventional model for mathematics achievement with the results of FA = 9.057277 (2) There are influence of the creativity of students on achievement learn math with the results of FB = 14.00357 (3) there is no interaction between learning model with mathematical creativity of students to learn mathematics achievement with FAB = 1.197401